Analise não-paramétrica da eficiência das unidades do IFTO: Aplicação de um modelo DEA - Carvalho, Leonardo Brasil (Universidade Federal do Tocantins, 2019)
Currently, in Brazil, has deepened a discussion of evaluation of public sector efficiency, especially at the public treasury expenditure policies that need to have specific purpose and objective. Some institutions, however, has its subjective purpose too abstract, as in the case of educational institutions. In this case, the evaluation goes through the productive work of the institution, which in such a company. How much of each resource is available for these institutions and that results explicitly or implicitly aims the society receives? To elucidate this question, this dissertation aims to provide a necessary part of the analysis and decision making. This is a specific case study of a set of 6 units from the Federal Institute of Tocantins (IFTO, in portuguese) with application of a Data Envelopment Analysis model. Data in various information systems available on vocational education and human resources were collected. By the model applied, view of the characteristics of the methodology, it was found that 4 of the 6 units are efficient and 2 units are inefficient. It was also noticed a considerable gap between the scores obtained by the efficient DMUs and inefficient. Finally, is analyzed the results obtained from the model applied, which shows, as most relevant aspect, the fact that units installed in cities which are regional center tends to be efficient, while units installed near the poles major cities tends inefficiency.